Carbon Nanotubes: Synthesis of PbI2 Single‐Layered Inorganic Nanotubes Encapsulated Within Carbon Nanotubes (Adv. Mater. 13/2014). (April 2014) - Cabana, Laura; Ballesteros, Belén; Batista, Eudar; Magén, César; Arenal, Raúl; Oró‐Solé, Judith; Rurali, Riccardo; Tobias, Gerard
<x xml:space="preserve">Abstract</x> An individual layer of lead iodide (depicted in the lower part of the image) is seamlessly wrapped into a cylinder, resulting in the formation of a single‐walled inorganic nanotube. To achive this, a solvent‐free high‐temperature route is employed using the inner cavities of multiwalled carbon nanotubes as hosting templates. This work is described by G. Tobias and co‐workers on page 2016. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>